Teaching in the middle and secondary schools - Kellough, Richard Dean (Allyn & Bacon, 2009)
"Teaching in the Middle and Secondary Schools, Ninth Edition, is a highly practical text for pre-service teachers in middle school and secondary methods courses. Readers will find useful, ready-to-use classroom applications for planning instruction, selecting and using instructional strategies, and assessment. Each module includes exercises and posttests."--Book jacket.